Traffic Impact Analysis of Zaenal Zakse Road Due to Kebalen Market Activities in Malang City: Analisis Dampak Lalu Lintas Jalan Zaenal Zakse Akibat Aktivitas Pasar Kebalen di Kota Malang - Primasworo, ST., MT, Rifky; Andy Kristafi Arifianto; Blima Oktaviastuti; Gilberd Herdani Hau Pia (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2025)
Community behavior in the market area has a direct impact on traffic flow, especially during peak hours when vehicles enter and exit the market. The presence of street vendors and illegal parking on the roadside exacerbates the problem by adding to traffic congestion, slowing traffic, and storing cars in certain areas. This study aims to determine traffic performance and the effect of Kebalen Market activities on traffic performance. The research design uses quantitative with descriptive research type. This research was conducted at Jalan Zaenal Zakse, Jodipan, Malang City using the Indonesian Road Capacity Guidelines (PKJI) method. The calculation results show that the traffic impact due to market activities has a negative impact on the performance of the Zaenal Zakse Road Section when viewed from the highest average degree of saturation on Sunday, November 3, 2024 at 06:00-07:00 am at 1.16 level of service F with the criteria for stuck / jammed flow.